Economic And Social Consequences of The Covid-19 Pandemic: The Experience of Ukraine and Sweden - Oksana MARUKHLENKO; Tetiana POSPIELOVA; Svitlana SOKOLOVSKA (Communications of International Proceedings, 2020)
The article examines the economic and social consequences of the COVID-19 pandemic. By constructing a multifactor regression model, the authors analyzed the economic and social indicators of development of Ukraine and Sweden, investigated the dependence of selected indicators on quarantine measures. In order to identify the basic patterns of development of economic and social processes under the influence of quarantine measures related to COVID-19, regression models of socialization of economic development were calculated. Indicators that during the correlation analysis revealed the greatest dependence on domestic policy and the level of economic development of regions in the conditions of COVID-19 were selected as dependent variables, namely: employment rate (%), average per capita disposable income (USD); indicators of economic development and financial condition of the regional budget: revenues of the regional budget per 1 person (USD), subventions from the state budget per 1 person (USD), gross national product per 1 person (USD), capital investments per 1 person (USD). The obtained regression parameters in the analyzed regions are equally targeted and show a direct relationship between the studied indicators of social development and regional budget revenues and inverse dependence on government subsidies, which confirms the reduction of this tool to influence the development of social sphere in the region under COVID-19. At the same time, there is a direct and stable relationship between local budget revenues and citizens' incomes. Regression models showed that in the conditions of COVID-19 both in Sweden and in Ukraine, the average per capita disposable income of the population directly depends on subventions from the state budget. Regression analysis showed a close link between quarantine measures related to the COVID-19 pandemic and the socio-economic development of Sweden and Ukraine.
Keywords: COVID-19; pandemic; economic and social consequences; public policy; Ukraine; Sweden.